2015 Nutrition profile: Global - International Food Policy Research Institute (International Food Policy Research Institute, 2015)
This is a snapshot of the global status of nutrition for each year the report covers. It highlights the global scale of the entire spectrum of malnutrition throughout the lifecycle, the wider determinants of nutrition, and the policy environment that influences nutrition. It complements individual country profiles and facilitates comparison of national-level data with the global situation.